Il magistero di un “maestro senza cattedra”. Sebastiano Timpanaro tra didattica e filologia classica - Fabi, Alessandro (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
This article aims to discuss some peculiarities of Sebastiano Timpanaro’s contribution in terms of didactics. Even if his intellectual activity evolved apart from academies – and despite the charming and abused image of the proofreader –, Timpanaro was able to transmit a methodological lesson widely recognized in a plurality of contexts. His handbooks reveal – once more – a well defined “scientific” imprinting: in conformity with his materialism (or “marxism-leopardism”), Timpanaro used to chase the objective truth by means of a systematic comparison between “sciences” and “humanities”. Although classical philology remained his main research field, his didactic approach made no distinction between specializations, focusing on single problems regardless of their nature. Timpanaro; Didactics; Philology; Method; Materialism.